2020
DOI: 10.1016/s2215-0366(19)30288-3
|View full text |Cite
|
Sign up to set email alerts
|

Understanding suicidal ideation and behaviour in individuals with chronic pain: a review of the role of novel transdiagnostic psychological factors

Abstract: Individuals with chronic pain are at elevated risk of suicide, yet psychosocial factors that may be involved in increasing or decreasing vulnerability for suicidal ideation and behaviour have received little attention. Extant literature on the topic of suicide in individuals with chronic pain only incorporates a limited number of the wide array of known vulnerability and protective factors from the field of suicide research. The current review focuses on transdiagnostic psychological processes, i.e. processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 70 publications
(112 reference statements)
2
20
0
1
Order By: Relevance
“…A positive, moderate, and statistically significant association has also been found between mental defeat and the worst suicide attempt [73]. The conceptual and methodological overlap between perception of defeat and mental defeat [27], together with the high perception of defeat presented by FM patients in the profile of high vulnerability to suicidal ideation, suggests a similar functioning of both constructs in people with chronic pain. Given that IMV [31] is one of the most prominent models in the field of suicide, the study of key variables and their association with the characteristics of the chronic pain population may help to explain suicidal ideation in these patients.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…A positive, moderate, and statistically significant association has also been found between mental defeat and the worst suicide attempt [73]. The conceptual and methodological overlap between perception of defeat and mental defeat [27], together with the high perception of defeat presented by FM patients in the profile of high vulnerability to suicidal ideation, suggests a similar functioning of both constructs in people with chronic pain. Given that IMV [31] is one of the most prominent models in the field of suicide, the study of key variables and their association with the characteristics of the chronic pain population may help to explain suicidal ideation in these patients.…”
Section: Discussionmentioning
confidence: 89%
“…According to the cry of pain theory hypothesis [37], suicidal ideation/intention arises when people feel defeated (i.e., perceived failed struggle and helplessness as a result of a loss or significant alteration of social status, identity, or goals) and there is no perceived escape or rescue from such a situation (i.e., entrapment). While the main assumptions of IMV have been supported empirically in previous studies [38][39][40][41], they have not been tested in people with chronic pain [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…66 In an attempt to better understand the complex pain-suicidality association in adults, a recent review has revealed psychological processes that are common to both conditions (e.g., psychological flexibility, future orientation and mental imagery). 67 However, it remains unknown whether these psychological processes may also drive the behavioural change that may explain the pain-suicidality relationship in adolescence. It is, therefore, essential to better understand the pain-suicidality trajectories and the potentially complex interplay with unique correlates in adolescence to identify these vulnerable youth.…”
Section: Discussionmentioning
confidence: 99%
“…Given suicide is a leading cause of death — particularly for young people 98 — and that depression and chronic pain are both treatable conditions, assessing their comorbidity in both at-risk youth and older adult populations may help to reduce suicide rates. 99102…”
Section: Discussionmentioning
confidence: 99%